Kajian Biofisik Lahan Untuk Tanaman Porang Sebagai Anasir Konservasi Pada Sistem Agroforestri Di Pulau Lombok - IGM Kusnarta; Mahrup Mahrup; Padusung Padusung; I Nym Soemeinaboedhy; Fahrudin Fahrudin (LPPM Universitas Mataram, 2021)
Agricultural land in North Lombok is dominated by a typology of sub-optimal land, physically, chemically and biologically. These properties make it vulnerable to degradation. In such land, agroforestry system is highly recommended, where the porang plant can be included as a component. Nowdays, porang is gaining popularity as a commodity with economic value, and is suitable as an intercropping plant. It is easy to grow on almost all types of soil, and is resistant to shade, making it adaptive to agroforestry systems as non-timber under standing plants in community forest systems. It is believed that this will provide multiple benefits economicly and environmentaly, if it accompanied by the principles of soil and water conservation. The role of porang as a conservative agent has been investigated through a scientific approach as the basis for the domistication of porang in agroforestry systems. The results showed that agroforestry with porang could help improve the stability of the soil aggregates as indicated by the soil aggregate stability index 59 which means rather stable. Soil moisture of wilting point in agroforestry system with porang increased from 3.0% (without porang) to 5.4%. In addition, the soil organic matter content increased to 3.94% (quite high) on the system with porang because the stems and leaves of porang plant are quickly weathered. The ground cover is relatively tight, so it can prevent soil erosion. Porang also play a role in increasing water infiltration due to the presence of porang’s roots and tubers. Thus the domistication of porang fulfills the requirements as an agent of soil conservation, as non-timber plant in the agroforestry system, if it is cultivated according to the principles of soil and water conservation on the typology of sub-optimal land in North Lombok.